Analysis of Supply Chain Pattern and Added Value of Processed Catfish (Clarias sp) Agroindustry in Hangtuah Village, Perhentian Raja Sub District, Kampar Regency, Riau Province - Silaban, Yunita Feronika Br.; Hendrik, Hendrik; Yolandika, Clara (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Hangtuah Village is known as